Organizational Commitment: Developing a Valid and Reliable Measuring Instrument - Sina, Aditya Citra Ibnu; Rahmasari, Dewi Hajar; Wijayadi, Dwiky Wahyu; Prasetya, Joshua Aljamo Christ; Maulidina, Nurul; Imha, Ulia Arbarehan; Suherman, Suherman (Universitas Islam Negeri Raden Intan Lampung, 2025)
Organizational commitment is crucial to study because high commitment is believed to be beneficial for both the organization and the employees themselves. When employees have a commitment to the organization, it leads to their optimal efforts, which are essential for achieving organizational goals. This study uses the organizational commitment theory developed by Allen and Meyer (1991), which encompasses three aspects: affective, continuance, and normative commitment. The theory was further developed into 47 items. The theory was chosen because it effectively represents the dimensions of organizational commitment and serves as a solution to enhance understanding and develop effective strategies to strengthen organizational commitment. The research was conducted at Hospital X with a population of 728 employees, and 202 research subjects were selected using simple random sampling. The research employed a quantitative method, and data collection was conducted using a Likert scale questionnaire. The results of the study revealed that out of the 47 items, 12 items were invalid, leaving 35 items that can measure the variable of organizational commitment.Keywords: Organizational Commitment, Psychological Scale, Measuring Instrument